Evaluation and management of nonsyndromic congenital hearing loss. Issue 5 (October 2017) - Funamura, Jamie L.
Abstract : Purpose of review: Nonsyndromic congenital hearing loss represents the largest proportion of paediatric sensorineural hearing loss. The optimal evaluation and management of affected patients remains clinically challenging. Current controversies in the diagnostic work-up of nonsyndromic congenital hearing loss are presented in this review. Recent findings: The improved diagnostic yield of comprehensive genetic testing due to new sequencing technologies is changing the diagnostic for congenital hearing loss. Concerns for both ionizing radiation and general anaesthetic exposure are also driving shifts in imaging modality preferences for infants and toddlers. Summary: A thoughtful systematic, targeted approach taking into consideration the audiologic phenotype of the patient is recommended for the work-up of nonsyndromic congenital hearing loss.